PENGELOLAAN PENDIDIKAN MADRASAH ALIYAH: TELAAH TERHADAP PERATURAN MENTERI PENDIDIKAN NASIONAL NO. 19 TAHUN 2007 TENTANG STANDAR PENGELOLAAN PENDIDIKAN - Yundri akhyar (AL-FIKRA, 2009)
Nowadays, the management of Madarasah Aliyah is not maximal yet. The quality of its management is still under of SMU. In fact, there is UU SIKDIKNAS eliminating the discrimination between the secular and religious education. This law is explained in PP. NO. 19 in 2005 about the standardization of national education. But it does not improve the quality of MA. This regulation is described in a detailed explanation in PP. NO. 19 in 2007 about the standardization of  education’s management. This clearly explain the management of MA, including the implementation of MA’s programs, funding, ethics, supervision, evaluation, leadership of MA, and information access. These are done based on independence, partnership, participation, transparency, and accountability. Therefore, the management of MA should be effective and efficient.